STRENGTHENING LITERACY THROUGH LIBRARY REVITALIZATION AND READING TREE INNOVATION - Arafah Mazaya; Rika Mutiara (LPPM Universitas Flores, 2026)
This community service program aims to improve students' literacy culture through library revitalisation and the development of literacy media, including